Enhancing Well-Being and Social Connectedness for Māori Elders Through a Peer Education (Tuakana-Teina) Programme: A Cross-Sectional Baseline Study - Oetzel, John G.; Ruru, Stacey; Zhang, Yingsha; Simpson, Mary Louisa; Nock, Sophie; Meha, Pare; Holmes, Kath; Clark, Marama; Adams, Hariata; Akapita, Ngapera; Ngaia, Kawarau; Murphy, Shane; et al. (Frontiers in Public Health, 2021)
Background Māori kaumātua (elders) face stark health and social inequities compared to non-Māori New Zealanders. The tuakana-teina (older sibling-younger sibling) peer education programme is a strengths-based approach to enhance wellbeing and social connectedness. The purpose of this study is to present the baseline data from this programme and identify correlates of wellbeing outcomes. Method Participants included 128 kaumātua who completed a self-report survey about health-related quality of life, spirituality, social connection and loneliness, life satisfaction, cultural identity and connection, elder abuse, health service utilisation and demographics. Findings Multiple regression models illustrated the following correlates of outcomes: (a) self-rated health: needing more help with daily tasks (β=-0.36) and housing problems (β=-0.17); (b) health-related quality of life: needing more help with daily tasks (β=-0.31), housing problems (β=-0.21), and perceived autonomy (β=0.19); (c) spiritual wellbeing: understanding of tikanga (cultural protocols) (β=0.32) and perceived autonomy (β=0.23); (d) life satisfaction: social support (β=0.23), sense of purpose (β=0.23), cultural identity (β=0.24), trouble paying bills (β=-0.16), and housing problems (β=-0.16); (e) loneliness: elder abuse (β=0.27), social support (β=-0.21), and missing pleasure of being with whānau (family) (β=0.19). Conclusions Key correlates for outcomes centred on social support, housing problems, cultural connection and perceived autonomy. These correlates are largely addressed through the programme where tuakana/peer educators provide support and links to social and health services to teina/peer recipients in need. This study illustrates needs and challenges for kaumātua, whilst the larger programme represents a strengths-based and culturally-centred approach to address health issues related to ageing in an Indigenous population.